Bratz Miss Fortune - Elliot, Rachel (London Parragon, 2007)
"The Bratz are totally stoked when a mysterious old lady gives them an ancient charm necklace, which brings them good luck and happiness. But their good luck turns to bad when the necklace falls into the hands of the troublemaking Tweevils. Will the Bratz be able to work together and realise that you can make your own luck or will the ancient necklace cause a rift so big that no charm could save them?"--Back cover.
Keywords: Quakers -- Charms